2015
DOI: 10.1049/mnl.2015.0198
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐plane buckled cantilever microstructures with adjustable angular positions using thermal bimorph actuation for transducer applications

Abstract: The integration of thermal bimorph actuators and buckled cantilever structures to form an out-of-plane plate with adjustable angular positions is reported. This structure could be used as a platform to build other transducers such as optical micromirrors, scanning antennas, switches or low-frequency oscillators. The electromechanical characterisation has shown that these structures can adjust their angular position by 6°when they are operated using a DC source. The thermal characterisation performed by an infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The use of polymerbased substrates to support thermoelectric (TE) materials is of special interest since highly advantageous inorganic materials can be integrated, including those with superior thermal and electrical properties [50]. An important advantage of polymer-based substrates, such polyimide (PI) [51] and SU8 [52], is their capability to form out of plane structures [53,54] and be used with more advanced photolithography-based fabrication techniques, which can offer greater resolutions, hence allowing the creation of more complex and compact implementations [51][52][53][54]. On the other hand, paper is a remarkable structural material which can be used to fabricate simple, affordable and flexible TEGs [55].…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymerbased substrates to support thermoelectric (TE) materials is of special interest since highly advantageous inorganic materials can be integrated, including those with superior thermal and electrical properties [50]. An important advantage of polymer-based substrates, such polyimide (PI) [51] and SU8 [52], is their capability to form out of plane structures [53,54] and be used with more advanced photolithography-based fabrication techniques, which can offer greater resolutions, hence allowing the creation of more complex and compact implementations [51][52][53][54]. On the other hand, paper is a remarkable structural material which can be used to fabricate simple, affordable and flexible TEGs [55].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] However, existing systems usually have folding angles of less than 90°, and have been difficult to integrate into origami designs with more complex motions and functions. Separate attempts have created 3D assembly with large folding angles using tradition MEMS processes, but these systems usually require manual assembly with probe stations [37][38][39] or through an applied magnetic field. [20][21][22][23][24] We show that with the proposed method, we can self-assemble the gripper and achieve a large gripping motion using the same base design.…”
Section: Controllable Multi-degree-of-freedom Shape Morphing For Compmentioning
confidence: 99%
“…Electro-thermal (ET) actuation is a popular transduction mechanism that can produce large folding motions actively. [3,4,18,37] Past research has shown that these systems are useful for building micro-cages, [3,4] micro-manipulators, [38] and micro-grippers. [24] Among ET actuators, polymer-based systems can provide superior folding capabilities because of the high thermalexpansion coefficient of polymeric materials.…”
Section: Introductionmentioning
confidence: 99%